If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 1 = 25 + -2x Reorder the terms: 1 + 4x = 25 + -2x Solving 1 + 4x = 25 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 1 + 4x + 2x = 25 + -2x + 2x Combine like terms: 4x + 2x = 6x 1 + 6x = 25 + -2x + 2x Combine like terms: -2x + 2x = 0 1 + 6x = 25 + 0 1 + 6x = 25 Add '-1' to each side of the equation. 1 + -1 + 6x = 25 + -1 Combine like terms: 1 + -1 = 0 0 + 6x = 25 + -1 6x = 25 + -1 Combine like terms: 25 + -1 = 24 6x = 24 Divide each side by '6'. x = 4 Simplifying x = 4
| 15o^2+36o+17=0 | | ln(3x)=5.82 | | y^2+-3y+-40=0 | | 4.9(x+5.1)=36.8 | | -6n=54 | | -9+n=-8 | | 11x-2=3x+11 | | o^2+0o+-4=0 | | -7=p-5 | | 6s^2+3s=0 | | 802.1-4.82+9= | | y-9=-19 | | 4r^2+30r+10=0 | | 24=4n | | 8(x+12)-288=3x | | 3q+4=2q+10 | | 2x^2+8x=192 | | 8x+35=6x+27 | | n^2+-3n+-40=0 | | 7x+1=52 | | 10v^2-21v-49=0 | | 2x^3+8x^2-64=0 | | n^2+2n+-24=0 | | -2(x+3)-2(-x+3)=6-x | | -4(-2)-4y=4 | | 7-3r=r-4(2-r) | | 0=4x^3-256x | | 4(3X)=158 | | 4c^2+36c-144=0 | | tan(y)=20 | | cos(6x)+cos(4x)+cos(2x)=0 | | 6w-2=2w+10 |